Potential of coagulation/GAC adsorption combined with UV/H2O2 and ozonation for removing dissolved organic matter from secondary RO concentrate. Issue 4 (30th November 2018) - Zhang, Xian; Lin, Jiuyang; Ye, Wenyuan; Zhou, Wei; Jia, Xuxiang; Zhao, Shuaifei; Ye, Chunsong
Abstract: BACKGROUD: Organic contaminants in secondary reverse osmosis (SRO) concentrate pose a severe threat to the ecosystem, due to their potential toxicity. In this study, potential of coagulation/granular activated carbon (GAC) adsorption combined with UV/H2 O2 and ozonation for removing organic matter from industrial secondary RO concentrate was systematically investigated. RESULTS: Coagulation with 2.0 mmol L −1 FeCl3 yielded 40% removal of dissolved organic carbon (DOC), while adsorption with 5 g L −1 GAC could boost the removal efficiency up to 78.2%. Fractionation results showed that both coagulation and GAC adsorption favored hydrophobic organics. UV/H2 O2 oxidation was capable of removing 87.4% of DOC, which outperformed ozonation (58.2%). UV/H2 O2 and ozonation showed similar behavior in dissolved organic matter (DOM) degradation: a portion of hydrophobic organics were first transformed into hydrophilic fractions prior to final mineralization. Conclusion: Coupling of GAC as post‐treatment with a UV/H2 O2 process yielded 97.9% removal of DOC and the corresponding electrical energy per order (EE/O) was decreased from 66.7 to 35.8 kWh m −3 . Consequently, a simple UV/H2 O2 and GAC hybrid process was proposed to be a suitable method for removing DOM from SRO concentrate. © 2018 Society of Chemical Industry